Continuous improvement towards environmental protection for pharmaceuticals: advancing a strategy for Europe - Sam Harrison; Catherine Barnett; Stephen Short; Cansu Uluseker; Patricia V. Silva; Maria D. Pavlaki; Sarah Roberts; Madalena Vieira; Stephen Lofts; Susana Loureiro; David J. Spurgeon (Environmental Sciences Europe)
Abstract The manufacture, use and disposal of pharmaceutical products can lead to their release into the environment, raising concerns about potential risks to biota and human health. This is recognised in the European Commission’s Pharmaceutical Strategy for Europe, which has recently overseen the development of a proposed revision of current pharmaceutical legislation. Amongst other things, this strategy and revision broadly offer strengthened protection against environmental risk. For example, it enhances the power authorities have to refuse market authorisation where an identified risk to the environment cannot be sufficiently addressed, includes a requirement for legacy pharmaceutical products to be risk assessed, includes a broadened scope to cover the entire product lifecycle, and places a greater focus on open data. In this publication, we assess the proposed legislation against the latest scientific knowledge, identifying opportunities for strengthening the protection that it offers. These opportunities include moving towards the risk assessment of mixtures, broadening the scope of effects testing to include non-conventional (e.g., behavioural) and chronic endpoints, making better use of predictive modelling such as Quantitative Structure–Activity Relationships (QSARs), and better accounting for environmental heterogeneity, such as the influence of temperature and especially pH on risk. Many of the elements discussed apply not just to pharmaceuticals but across other chemical domains and regulatory regimes, particularly when considering mixture assessment. Integrating knowledge across sectors and regulatory regimes is therefore crucial to better address the role of pharmaceuticals as one of many environmental pollutants.